The Influence of Market Orientation on Business Performance of Micro, Small, and Medium Enterprises Through Innovativeness - Nasrah, Rasidah; Husin, Nor Azilah; Salleh, Noor Akma Mohd (Advances in Social Sciences Research Journal, 2023)
The new era affects the world of industry and business, including small and medium companies such as Micro, Small, and Medium Enterprises (MSMEs). MSMEs have a strategic and significant role in the economy and then contributed to increasing foreign exchanges through export-import activities. However, MSMEs in Indonesia are facing various problems such as limited modality, low-quality human resources, mastery of science and technology, and the dependence of the domestic industry on imported raw materials. They reduce the purchasing power and slow industrial growth in Indonesia. Therefore, this study conducts to find out the influence orientation market on the performance of MSMEs in Payakumbuh. This study used quantitative methods and data collection by distributing questionnaires. The unit of analysis in this study is traditional crackers (Kerupuk) from Indonesia MSMEs while the observation unit is the owner or manager. The population of the study was 285 MSMEs owners or managers. The results of this research found that the orientation market has a significant effect on business performance and innovation Kerupuk MSMEs in Payakumbuh. Innovation also has a significant effect on MSME’s Performance. However, innovation has shown no effect between the orientation market and business.